An analysis of determinants affecting entrepreneurial intention among students at UC Makassar / Justin Wijaya ... [et al.] - Wijaya, Justin; Putra, Sinar Dharmayana; Triany, Novika Ayu; Jafar, Adindah Novihartina; Perdana, Cipta Canggih; Simanungkalit, Novalina Gloria (2023)
The study of entrepreneurship is widely prevalent in education, particularly at the higher education level, with Indonesia being no exception. The presence of one of the programmes under the Ministry of Education and Culture (Mendikbud), namely the Independent Learning Campus (MBKM), is evidence of the emphasis placed on entrepreneurship. This initiative promotes the incorporation of entrepreneurial courses into the curricula of educational institutions. When developing the curriculum, educational institutions should possess an understanding of the determinants that foster entrepreneurial aspirations. This study aimed to ascertain the determinants that foster entrepreneurial inclinations among students at UC Makassar. The research was undertaken from June to July 2023, focusing on students enrolled at UC Makassar who completed at least one year of study. The study included a total of 34 participants, who were students from various academic disciplines at UC Makassar. The research method employed in this study was a quantitative approach, which was assessed through the SmartPLS software. The findings of this study indicated that the perceived Desirability, Feasibility, and inclination to act are influential factors in fostering entrepreneurial intention among students at UC Makassar.